2004
DOI: 10.1007/s11255-004-8788-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in uremic symptoms after increasing daily dialysate volume in patients on chronic peritoneal dialysis with declining renal function

Abstract: The prevalence of all uremic symptoms decreased significantly after the daily dialysate volume was increased. The improvement in symptoms despite the decline in residual function emphasizes the beneficial effect of increased dialysate volume, which produced a significantly higher peritoneal creatinine clearance and Kt/V after the change in the PD prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
(20 reference statements)
1
12
1
Order By: Relevance
“…A spectacular correction of sleep apnea was recorded in this small-scale study [44]. Furthermore, increasing the dialysis dose was associated with an improvement in sleep in 50% of peritoneal dialysis patients [45]. Finally, the impact of uremic toxins is highlighted by the fact that sleep disorders are more frequent and more severe in dialyzed patients compared with subjects with pre-dialysis CKD [18].…”
Section: Uremic Toxinsmentioning
confidence: 68%
“…A spectacular correction of sleep apnea was recorded in this small-scale study [44]. Furthermore, increasing the dialysis dose was associated with an improvement in sleep in 50% of peritoneal dialysis patients [45]. Finally, the impact of uremic toxins is highlighted by the fact that sleep disorders are more frequent and more severe in dialyzed patients compared with subjects with pre-dialysis CKD [18].…”
Section: Uremic Toxinsmentioning
confidence: 68%
“…Previously, Graf et al [28] reported that lowering the dialysate magnesium concentration can restore nerve conduction velocity towards normal in patients receiving HD, and this could be the reason for the complete disappearance of pruritus in the study by Hiroshige et al [24]. In contrast, Carmichael et al [29] failed to demonstrate a beneficial effect of reduction in magnesium on pruritus.…”
Section: Modification Of Dialysis Techniquesmentioning
confidence: 97%
“…However, it still remains uncertain whether alterations in dialysis therapy including changes in dialysis membrane can reduce pruritus [24] [25] or not [26]. Hiroshige et al [27] analyzed data on 59 HD patients, who did not have disorders in calcium and phosphate metabolism, and found that more than 60% of them suffered from disabling pruritus possibly related to chronic uremia.…”
Section: Modification Of Dialysis Techniquesmentioning
confidence: 99%
“…In PD, one study also reported an improvement in appetite scales through applying increased daily dialysate volume [89]. In fact, the increase in the number of dialysis sessions through short daily HD or nocturnal HD has been shown to improve appetite and food intake [85e88].…”
Section: Treatment Of Anorexia In Ckdmentioning
confidence: 99%